AN ANALYSIS OF THE INSTITUTIONAL STRUCTURE OF ZAKAT AND THE CASE FOR TURKEY - Fatma Nur Zagrali (Share: Jurnal Ekonomi dan Keuangan Islam, 2017)
Poverty is a challenge the humanity has been facing for ages. Although it is possible to opine some amelioration of the acuteness of poverty in proportion to the world's population, the urge to fight against poverty needs to be preserved especially for the 1.2 billion people still living in extreme poverty. Taking poverty as the principal concern, this study tackles with some practical issues regarding zakat; which is an act of worship blending economic, social, political, moral and religious components to entail the solution of poverty. This study is aimed to (i) discuss the relation between zakat and poverty; (ii) present Turkish framework and locate the Presidency of Religious Affairs in search for a good governance of zakat; and (iii) propound a new institutional structure of zakat, with a renewed call for voluntary-based zakat collection and distribution system under the supervision of the Presidency of Religious Affairs. =========================================== Kemiskinan adalah tantangan yang dihadapi manusia selama berabad-abad. Meskipun mungkin untuk mengurangi beberapa perbaikan ketajaman kemiskinan sebanding dengan populasi dunia, dorongan untuk memerangi kemiskinan perlu dipelihara terutama untuk 1,2 miliar orang yang masih hidup dalam kemiskinan ekstrim. Kemiskinan merupakan persoalan yang perlu diperhatikan, penelitian ini mengkaji beberapa masalah praktis mengenai zakat; Yang merupakan tindakan yang memadukan komponen ekonomi, sosial, politik, moral dan agama untuk mendapatkan solusi kemiskinan. Penelitian ini bertujuan untuk: (i) membahas hubungan antara zakat dan kemiskinan; (Ii) menyajikan kerangka Turki dan menemukan Kepresidenan Urusan Agama untuk mencari tata pemerintahan zakat yang baik; Dan (iii) mengemukakan struktur kelembagaan zakat yang baru, dengan seruan baru untuk pengumpulan dan distribusi zakat berbasis sukarela di bawah pengawasan Kepresidenan Urusan Agama.